Quality of working life and engagement in hostels - Wahlberg, T. A.; Ramalho, N.; Brochado, A. (Tourism Review, 2017)
Purpose: Hostels’ competitiveness relies heavily on unique and genuine service and, thus, counts on employees actively creating a social, welcoming environment and, at the same time, caring about – and being loyal to – their hostel. This paper aims to investigate whether retaining employees who care about their hostel and refrain from destructive behaviours implies that these workers need to have a better quality of working life, as well as whether work engagement mediates this relationship. Design/methodology/approach: A survey was conducted with 98 employees from 40 hostels in Lisbon. An analysis of the survey data was performed to test the research hypotheses. The model was estimated by means of partial least squares structural equation modelling. Findings: The results reveal that quality of working life has a strong negative impact on employees’ exit behaviours and a positive effect on their loyalty. In addition, work engagement was found to mediate fully the relationship between quality of working life and both employee voice and neglect, as well as partially mediating exit intentions. Originality/value: This study extended prior research in two ways. First, most theoretical and empirical studies in the hospitality and tourism industry have focused on hotels, so this research targeted a new context (i.e. hostels). Second, this study offers a clear indication of the relationship between employees’ quality of working life, work engagement and behaviours, thus offering valuable insights for management and hostel staff.